Słyszące rodzeństwo osób z wadą słuchu (SODA) – studium indywidualnych przypadków - Rożek, Aleksandra (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article describes the functioning of hearing siblings of persons with hearing loss in different developmental stages: childhood, adolescence and adulthood. It describes the key factors to the formation of positive relationships between deaf and hearing siblings. These may influence the psychosocial functioning of hearing people in adulthood.